Variability of DOC and nitrate responses to storms in a small Mediterranean forested catchment - Susana Bernal; Susana Bernal; Andrea Butturini; Francesc Sabater (Hydrology and Earth System Sciences, 2002)
Severe drought periods followed by intense rainfall often leads to major floods in Mediterranean catchments. The resulting hydrology is complex and the response of solutes in the streams is often unpredictable. This study aimed to identify the most relevant factors controlling the hydrological responses to storms of an intermittent Mediterranean stream and to link those factors with dissolved organic carbon (DOC) and nitrate during storm events. Measurements of climate, hydrology, DOC and nitrate concentrations during 26 storm events over three hydrological years were analysed. The contribution of the storm events to the total DOC and nitrate annual export was also calculated. Nitrate was mainly mobilised during high flow, while most of the DOC export occurred during baseflow. Solute concentrations peaked after drought periods and the solute export was maximal during the largest rainfalls (i.e. > 100 L m-2). One single large storm contributed some 22% of the total annual export of DOC, and about 80% of that of nitrate. Discharge was a good predictor of neither DOC nor nitrate responses, so variables other than discharge were considered. Factor Analysis was used to identify the main factors controlling the biogeochemical responses. Antecedent moisture conditions and the magnitude of the storm event were the most relevant factors and accounted for 63% of the total variance. Solute responses during high flow were highly variable. However, solute concentration changes showed a significant and moderate relationship with the factors controlling the hydrological responses (i.e. Δ DOC v. the antecedent moisture conditions and Δ NO3-N v. the magnitude of the storm event). Keywords: dissolved organic carbon, nitrate, Mediterranean, drought, Fuirosos catchment, storms